Cinematic Verbalists : Dialogue Integration in the Work of Selected Contemporary American Writer-Directors - O'Meara, Jennifer (Trinity College (Dublin, Ireland). Department of Film, 2015)
This thesis contributes to the study of dialogue in cinema, an area that remains critically under-developed within film studies. In general, scholarly references to speech tend to be made in passing, disregarding dialogue's role in audiences' experience of cinema and the tendency for lines of dialogue to be extracted and repeated. Resistance to speech dates back to the transition from silent film to 'talkies', when dialogue was received as unnecessary to cinema, initially considered to be a distinctly visual medium. Within academic criticism, analyses of dialogue remain few and far between. Dialogue is often paraphrased in summaries of plot or character, ignoring the narrative or aesthetic significance of the wording or delivery. Indeed, excluding analyses of voice-over narration, it is only since Sarah Kozloff's critical reappraisal of speech in Overhearing Film Dialogue (2000) that the subject has begun to receive sustained attention. In addition to Kozloff's focus on generic dialogue, further studies have emerged on dialogue's relationship to genre and cultural representation (ed. Jaeckle, 2013), classical female dialogue (DiBattista, 2001), and the verbal styles of individual filmmakers such as John Cassavetes (Berliner, 1999) and Preston Sturges (McElhaney, 2006).
Embargo End Date: 2022-01-01
Keywords: Drama, Film & Music, Ph.D.; Ph.D. Trinity College Dublin, 2015